The Effect of High Quality Feed Supplement on Growth Performance Post-Weaning Calves - Besse Mahbuba We Tenri Gading; Panjono Panjono; Ali Agus (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This research aimed to evaluate the effect of high quality feed supplement (HQFS) in growth performance of post-weaning calves. Twenty four calves post-weaning aged 6 months old, consisting of 12 males and 12 females, randomly divided into 2 groups, each group consisting of 6 calves. Grouping male and female calves fed control feed plus HQFS, was formulated from corn grain, corn gluten meal (CGM), pollard, soybean meal (SBM), wheat flour and agromix booster (treatment diet) as first group (treatment), and the second group was fed control feed without addition of HQFS (control). This study was conducted for 6 weeks. The variables observed included feed intake (dry matter, crude protein, and TDN), weight gain, feed conversion, feed cost per gain and body size (body length, chest girth, and withers height). The treatment was in factorial 2x2 in a Completely Randomized Design (CRD). Growth performance of post weaning calves were analyzed as repeated measures with feed (treatment and control) and sex (male and female) as factors. Results showed that the CP consumption, ADG and chest girth of treatment group was higher than (P<0.01) than the control group (0.42 and 0.34 kg/d, 0.95 and 0.71 kg/d, and 12.41 and 8.25 cm). TDN consumption, feed conversion, and body length of the treatment group were higher (P<0.05) than the control group (3.08 and 2.57 kg/d, 3.64 and 4.86, and 8.12 and 5.95 cm). DM consumption, chest girth and feed cost per gain of treatment and control group were not significant (3.87 and 3.69 kg/d, 7.30 and 6.72 cm, and IDR 16,280.00 and IDR 19,167.00). There was no difference between the growth of post-weaning calves between the male and female groups. There was no interaction between feed type and sex of the post-weaning calves. The conclusion of this study was that post-weaning calves fed HQFS (20.2%) produced better growth performance than controls.